Interrelationship of Global Social Responsibility and Social Loafing (the Case of Public Servants of Turkey) - Sadykova, Guzel; Cetin, Sefa; Atas, Huseyin (The Russian Academy of Sciences, 2020)
The article analyzes the relationship of indicators of global social responsibility and social loafing on the basis of a survey of public servants of the Turkish region of Kastamonu. Global social responsibility can be interpreted as the awareness of the need to preserve the stability of the world and social well-being. Social loafing assumes a significant decrease in the personal productivity of the group members during collective activity. This study revealed a negative correlation between aspects of global social responsibility and social loafing. The results indicate a polarity of these phenomena and are explained by mutually exclusive concepts of global social responsibility and social loafing; while the first personifies the constructive mechanism of social stability, the second is the destructive evasion of social identification and atrophy of values. In this context, an individual who is both an object and a subject of responsibility due to the influence of social norms, principles and values, must develop in terms of maintaining conscientiousness, spirituality, social inclusion and the implementation of humanization of society.
Keywords: 1. No poverty; 10. No inequality; 12. Responsible consumption